Auditoría de Cumplimiento Ambiental a la Junta Provincial de la Cruz Roja de Loja, Período 2022 - Campoverde Chamba, Ruth Enemay (2025)
The research titled: ENVIROMENTAL COMPLIANCE AUDIT OF THE PROVINCIAL BOARD OF THE RED CROOSS OF LOJA, 2022 PERIOD was conducted to verify the current status of the entity in relation to environmental regulation and standards. The aim was to determine the degree of compliance with environmental provisions and to prepare a report with the obtained results. The processes carried out for this work align with the three phases of an environmental compliance audit: 1. Planning or Pre-Audit: This phase involves preliminary knowledge, including an initial visit to gain a clear understanding of the entity’s situation. 2. Execution or On-Site Audit: This includes applying audit programs, developing procedures through the preparation of a legal requirements identification matrix, evaluating internal environmental control compliance, and preparing working papers to support the report. 3. Final Report or Post-Audit: This phase involves drafting and presenting the final result obtained during the environmental audit process. As a result, several deficiencies were identified, such as the lack of maintenance records for the emergency generator, the absence of records on common waste management, and the distribution of personal protective equipment (PPE) without proper documentation. These issues raised concerns regarding compliance with regulations and environmental responsibility. Following the audit, an environmental compliance audit report was prepared, providing a comprehensive overview of the findings and evidence collected, which are detailed in the comments, conclusion, and suggested recommendations. These recommendations must be implemented to enhance the entity’s environmental management.